2023
DOI: 10.4103/ijo.ijo_2817_22
|View full text |Cite
|
Sign up to set email alerts
|

Keratoprosthesis in dry eye disease

Abstract: Bilateral corneal blindness with severe dry eye disease (DED), total limbal stem cell deficiency with underlying corneal stromal scarring and vascularization, combined with adnexal complications secondary to chronic cicatrizing conjunctivitis is a highly complex situation to treat. In such eyes, procedures such as penetrating keratoplasty alone or combined with limbal stem cell transplantation are doomed to fail. In these eyes, keratoprosthesis (Kpro) or an artificial cornea is the most viable option, eliminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
(134 reference statements)
0
7
0
Order By: Relevance
“…[ 3 ]) in the outcomes section (page 1161) of their article. [ 1 ] Of note, our retrospective study, which included 82 eyes with up to 30 years of follow-up, demonstrated that the original OOKP technique by Strampelli resulted in better anatomical and functional outcomes when compared to other types of prostheses, including the MOOKP.…”
mentioning
confidence: 91%
See 3 more Smart Citations
“…[ 3 ]) in the outcomes section (page 1161) of their article. [ 1 ] Of note, our retrospective study, which included 82 eyes with up to 30 years of follow-up, demonstrated that the original OOKP technique by Strampelli resulted in better anatomical and functional outcomes when compared to other types of prostheses, including the MOOKP.…”
mentioning
confidence: 91%
“…With reference to the recent article “Keratoprosthesis in Dry Eye Disease” by Sharma et al ,[ 1 ] published in your journal, we wish to extend our congratulations to the authors for their comprehensive review article and thank them for the inclusion of our publication, “Osteo-odonto-keratoprosthesis According to Strampelli Original Technique: A Retrospective Study With Up to 30 Years of Follow-up” in the American Journal of Ophthalmology in May 2022. [ 2 ] However, we have identified a few inaccuracies that we would like to clarify to enhance the quality of the work.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We thank the authors of the letter to the editor for their interest and comments regarding our review article titled ‘Keratoprosthesis in Dry eye disease’. [ 1 2 ] Thank you for the clarifications. In our manuscript, in Table 3, we have mentioned the most common etiology for Osteo-Odonto-Keratoprosthesis (OOKP) in the paper by Iannetti et al .…”
mentioning
confidence: 99%